2022
DOI: 10.3390/su14106022
|View full text |Cite
|
Sign up to set email alerts
|

Legume Integration Augments the Forage Productivity and Quality in Maize-Based System in the Loess Plateau Region

Abstract: The changing climate, inadequate water supply, insufficient agricultural inputs, decreasing in agricultural arable land areas under forage crops of Northwestern Loess Plateau region, expanding livestock population, increasing demands for meat and milk production, and food and feed security concerns all insist on a necessary requirement in forage quality production. Cereal–legume mixed-cropping is a biological approach to enhancing herbage yield and quality of upgraded animal feed (forage and silage). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Similar to the previous study’s findings, NDF and ADF were found to have a positive connection with CP. On the other hand, the association between CP, CF, and NDF was reported to be negative by Soe Htet et al [ 14 ] and Chaudhary et al [ 47 ]. Conversely, Be’langer et al [ 31 ] proposed an enhanced connection between nutritional concentrations with no negative effects on pasture quality by combining timothy and alfalfa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the previous study’s findings, NDF and ADF were found to have a positive connection with CP. On the other hand, the association between CP, CF, and NDF was reported to be negative by Soe Htet et al [ 14 ] and Chaudhary et al [ 47 ]. Conversely, Be’langer et al [ 31 ] proposed an enhanced connection between nutritional concentrations with no negative effects on pasture quality by combining timothy and alfalfa.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers suggest that cereal–legume intercropping can increase yields while also improving forage quality and nutritional composition [ 13 ]. Soe Htet et al analyzed the higher fresh biomass yield and dry matter yield in the cereal–legume cropping combination in terms of a mixture of maize and common bean [ 14 ]. As well, the previous study determined that cereal (wheat, ryegrass) and legume (alfalfa) mixed cropping showed increased production of dry matter yield, fresh biomass yield, and crude protein yield [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of each trait were expressed as a percentage of dry matter and mean values were used for downstream analysis. The relative feed value (RFV) was calculated based on the ADF and NDF concentrations according to the following formula provided by Htet et al (2022): DDMDigestibledrymatter=88.900.77×ADF. DMIDrymatter intake=120/NDF. RFV=DDM×DMI/1.29. …”
Section: Methodsmentioning
confidence: 99%
“…The WSC is another important forage quality indicator that has a significant impact on forage resistance to cold temperatures and grazing. Therefore, WSC is the most important qualitative attribute after DMI (Soe Htet et al, 2022). Soluble carbohydrates constitute a major part of non-structural carbohydrates, which provide energy for rumen microorganisms and maintain animal digestive health.…”
Section: Forage Qualitymentioning
confidence: 99%